Verbal memory decline from hippocampal depth electrodes in temporal lobe surgery for epilepsy. (3rd November 2017) - Ljung, Hanna; Nordlund, Arto; Strandberg, Maria; Bengzon, Johan; Källén, Kristina
Summary: Objective: To explore whether patients with refractory mesial temporal lobe epilepsy risk aggravated verbal memory loss from intracranial electroencephalography (EEG) recording with longitudinal hippocampal electrodes in the language‐dominant hemisphere. Methods: A long‐term neuropsychological follow‐up (mean 61.5 months, range 22–111 months) was performed in 40 patients after ictal registration with left hippocampal depth electrodes (study group, n = 16) or no invasive EEG, only extracranial registration (reference group, n = 24). The groups were equal with respect to education, age at seizure onset, epilepsy duration, and prevalence of pharmacoresistant temporal lobe epilepsy (TLE; 75%) versus seizure freedom (25%). Retrospective neuropsychological data from preoperative surgical workup (T1) and prospective follow‐up neuropsychological data (T2) were compared. A ≥1 SD intrapatient decline was considered as clinically relevant deterioration of verbal memory. Results: Significant decline in verbal memory was seen in 56% of the patients in the study group compared to 21% in the reference group. At T1, there were no statistical between‐group differences in memory performance. At T2, between‐group comparison showed significantly greater verbal memory decline for the study group (Claeson Dahl Learning and Retention Test, Verbal Learning : p = 0.05; Rey Auditory Verbal Learning Test, Total Learning : p = 0.04; Claeson Dahl Learning and Retention Test, Verbal Retention : p = 0.04). An odds ratio (OR) of 7.1 (90% confidence interval [CI] 1.3–37.7) for verbal memory decline was seen if right temporal lobe resection (R TLR) had been performed between T1 and T2. The difference between groups remained unchanged when patients who had undergone R TLR were excluded from the analysis, with a remaining aggravated significant decline in verbal memory performance for the study group compared to the reference group. Significance: Our results suggest a risk of verbal memory deterioration after the use of depth electrodes along the longitudinal axis of the hippocampus. Until this issue is further investigated, caution regarding depth electrodes in the language‐dominant hemisphere hippocampus seems advisable.